THE SCALE OF PRIORITY FOR THE CONSTRUCTION OF IRRIGATION CHANNELS FOR STAKEHOLDERS PERCEPTIONS OF THE IRRIGATION SERVICE IN SIDOARJO REGENCY - George Winaktu; Lalu Mulyadi; Edi Hargono DP (Universitas Islam Malang, 2020)
Sidoarjo Regency is one of the megapolitan Gerbang Kertosusilo. The planted area during the rainy season and dry season reaches 30,000 ha. The area of paddy fields continues to decline, namely 26,334 ha (2002), 22,460 ha (2010), and an estimated 13,544 ha (2009–2029). Sidoarjo Regency Irrigation Service as executor of irrigation management is of course inseparable from construction project activities. In the implementation of the construction of new irrigation networks as well as in rehabilitation and maintenance, it is necessary to implement project management. Before the project is implemented, it must first be submitted through proposals from the village level. In following up the proposal the writer used the Analytic Hierarchy Process (AHP) analysis method. With four aspects that affect the determination of the proposal: The results of the analysis obtained the weight of each criterion as follows: Service Area (ha) 0.3179, Cost 0.3159, Benefits 0.3217, and Network Conditions 0.0445. The results of the above analysis obtained priority ranking from the first to the last sequence as follows: Plengsengan Gedangrowo Channel, Normalization of Reform Channels, Installation of floodgates, Plengsengan ChannelsDs. Suwaluh, Rehabilitation of Ketawang Canal Kec. Sukodono, Rehabilitation of Candi Subdistrict Channel, Plengsengan Channel Ds. Suwaluh, Plengsengan Channels Purboyo II Ds. Popoh, Plengsengan Irrigation Channels Dsn. Kesimbuk, Plengsengan Channel Mangetan Kanal.